2015
DOI: 10.3846/20294913.2014.994052
|View full text |Cite
|
Sign up to set email alerts
|

Assesment of the Industry Competitiveness of the Baltic States in the Eu During the Period of Economic Recession

Abstract: The purpose of the article is to carry out the assessment of the industrial competitiveness of the Baltic States in the EU during the period of economic recession. Revealed comparative advantage (RCA) and Symmetric index (SI) index values revealed that after the period of economic recession, the growth of the industrial competitiveness of the Baltic States, considering it from export positions, is slower in comparison with GDP changes. Latvia has taken strong competitive positions in the industry of raw materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It worth noting that the obstacles highlighted by SQU students are also highlighted by the results of other studies conducted in other universities and countries [36,37,33]. According to [38], a lack of entrepreneurship knowledge and skills is one of the main barriers for students to start their own businesses. The equipment of entrepreneurship knowledge and skills is very important to enhance students' confidence and interest of risk-taking, which are important factors to start new businesses [39,40].…”
Section: Discussionmentioning
confidence: 90%
“…It worth noting that the obstacles highlighted by SQU students are also highlighted by the results of other studies conducted in other universities and countries [36,37,33]. According to [38], a lack of entrepreneurship knowledge and skills is one of the main barriers for students to start their own businesses. The equipment of entrepreneurship knowledge and skills is very important to enhance students' confidence and interest of risk-taking, which are important factors to start new businesses [39,40].…”
Section: Discussionmentioning
confidence: 90%
“…It is observed that banks that lend funds to uneducated entrepreneurs lose money because there are no returns, due to the business owners' lack of business skills. Remeikiene et al (2013) concluded that business education for economics students offers a positive involvement towards developing students' entrepreneurial intentions as education is observed to be the greatest motivator. A university education offered them valuable knowledge about business and their studies developed personality traits as well as exposed them to external opportunities for entrepreneurial futures when associated with engineering students.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Papers related to the research aim present results focused on the readiness of businesses for Industry 4.0 (Ślusarczyk, 2018); the readiness of cities for Industry 4.0 (Nick & Pongrácz, 2016); Industry 4.0 and competitiveness (Bal & Erkan, 2019); industrial competitiveness of the Baltic States (Remeikiene et al, 2015), new trends of development of beer industry in Lithuania (Petraškevičius & Nedelko, 2017), factors which limit the application of Building Information Modelling in the construction industry (Sun et al, 2017); smart factory performance and Industry 4.0 (Büchi et al, 2020); Industry 4.0 learning factory for regional SMEs (Faller & Feldmüller, 2015); challenges of Industry 4.0 for small and medium-sized enterprises (Schröder, 2016); identification of the factors that affect the introduction of Industry 4.0 elements to small and medium-sized enterprises (SMEs) (Vrchota et al, 2019); the main economic factors of sustainable manufacturing within the industrial policy concept of Industry 4.0 (Frolov et al, 2017); a conceptual approach to introduce an integrated model improving SMEs e-business technologies (Neykova & Miltchev, 2019); technology challenges of sustainable business performance (Haseeb et al, 2019); service innovation and smart analytics for Industry 4.0 and big data environment (Lee et al, 2014); the Industry 4.0 revolution and the future of Manufacturing Execution Systems (MES) (Almada-Lobo, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%